Rare earth phosphate water-based antirust coating and preparation method thereof

By using rare earth phosphates as rust-preventive fillers and combining them with additives such as acrylic resins, a rare earth phosphate aqueous rust-preventive coating was prepared. This solved the problems of poor anti-corrosion performance and environmental protection restrictions of water-based coatings, achieving a highly efficient and environmentally friendly rust-preventive effect.

CN119350932APending Publication Date: 2025-01-24SHANGHAI UNIV OF ENG SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411727630.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-05
Filing Date
2024-11-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing water-based coatings have poor anti-corrosion performance, and traditional phosphate anti-corrosion technology is restricted by environmental regulations. Therefore, there is a need to develop environmentally friendly phosphate-based water-based anti-rust coatings.

Method used

Rare earth phosphates are used as rust-preventive fillers, combined with acrylic resins and other additives, to prepare rare earth phosphate salt-based rust-preventive coatings through high-temperature curing. The formulation includes deionized water, dispersant, wetting agent, defoamer, etc. The preparation process is simple and environmentally friendly.

Benefits of technology

Rare earth phosphate salt-based anti-rust coatings have good anti-rust properties, mechanical properties and hydrophobicity, are environmentally friendly, easy to mass-produce and have low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350932A_ABST
    Figure CN119350932A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth phosphate water-based antirust coating and a preparation method thereof. The rare earth phosphate water-based antirust coating comprises the following components in parts by mass: 12-14 parts of deionized water; 50 to 55 parts by mass of acrylic resin; 4.0-4.5 parts by mass of a dispersant; 0.2 to 0.4 part by mass of a wetting agent; 0.2 to 0.5 part by mass of a pH regulator; 0.3 to 0.5 part by mass of a defoaming agent; 0.8 to 1 part by mass of texanol; 0.2 to 0.3 part by mass of a leveling agent; 0.1 to 0.3 part by mass of a thickening agent; 0.1-0.2 part by mass of a 30% sodium nitrite aqueous solution; 0.05 to 0.1 part by mass of an antibacterial agent; and 1-4 parts by mass of rare earth phosphate. The water-based paint obtained by taking the rare earth phosphate as an anti-rust filler has good anti-rust performance, is green and environment-friendly, and also has excellent mechanical property, hydrophobicity and comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rare earth phosphate liquid antirust coating and a preparation method thereof, belonging to the technical field of antirust coatings. Background Art

[0002] Metal corrosion is a common phenomenon that not only destroys the aesthetics of metal, but also seriously affects its service life and safety. Applying a layer of anti-rust paint on the metal surface is the main measure to prevent metal corrosion and extend its service life.

[0003] Compared with organic solvent-based paint, water-based paint is a kind of paint that contains no or little solvent, and has the advantages of energy saving, environmental protection, and low pollution. However, the anti-corrosion performance of water-based paint is poor, and rust inhibitors need to be added to the coating to increase its anti-corrosion performance.

[0004] As an important rust inhibitor, phosphate plays a pivotal role in the field of metal corrosion protection. The main anti-corrosion and anti-rust functions of phosphate are achieved through its passivation effect; when the phosphate solution touches the metal surface, a thick oxide coating is generated. This coating can successfully isolate the metal from the outside world to prevent the metal from being damaged. At present, phosphates have been widely used in various metal corrosion protection fields. For example, in the construction industry, phosphates are used in anti-rust coatings, concrete additives, etc. to extend the service life of building materials. In the automotive industry, phosphates are used for anti-corrosion treatment of automobile chassis, body and other parts to improve the safety and durability of automobiles. In addition, phosphates also play an important anti-corrosion role in the fields of petroleum, chemical industry, electricity, etc.

[0005] Although phosphates have achieved remarkable application results in the field of metal corrosion protection, they still face some challenges. For example, with the continuous improvement of environmental protection requirements, traditional phosphate corrosion protection technology may be restricted. EU environmental protection regulation 1999 / 45 / EC stipulates that if the zinc compounds (such as zinc oxide, zinc phosphate, etc.) in the coating exceed the specified amount, they must be indicated in the packaging container, thereby limiting the use of traditional phosphate corrosion protection technology represented by zinc phosphate. Therefore, it is necessary to develop an environmentally friendly phosphate water-based anti-rust coating to replace the traditional zinc phosphate anti-rust coating. Summary of the invention

[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a rare earth phosphate liquid anti-rust coating and a preparation method thereof.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] A rare earth phosphate liquid anti-rust coating having the following composition and proportion:

[0009] Deionized water: 12-14 parts by weight;

[0010] Acrylic resin: 50-55 parts by mass;

[0011] Dispersant: 4.0~4.5 parts by mass;

[0012] Wetting agent: 0.2~0.4 parts by mass;

[0013] PH regulator: 0.2~0.5 parts by mass;

[0014] Defoaming agent: 0.3~0.5 parts by mass;

[0015] Alcohol ester twelve: 0.8~1 parts by mass;

[0016] Leveling agent: 0.2~0.3 parts by mass;

[0017] Thickener: 0.1~0.3 parts by mass;

[0018] 30% sodium nitrite aqueous solution: 0.1-0.2 parts by mass;

[0019] Antibacterial agent: 0.05~0.1 parts by mass;

[0020] Rare earth phosphate: 1-4 parts by mass.

[0021] In one embodiment, the acrylic resin is D012 acrylic resin latex.

[0022] In one embodiment, the dispersant is selected from any one of dispersants G5040 and G5100; and the rare earth phosphate is selected from any one of CePO4 and GdPO4.

[0023] In one embodiment, the wetting agent is wetting agent R-33; the pH regulator is DMAE; the defoaming agent is defoaming agent 825; the leveling agent is leveling agent 3020; the thickener is thickener 105A; and the antibacterial agent is 10% DF35 aqueous solution.

[0024] In one embodiment, the rare earth phosphate is prepared by using rare earth metal oxide and NH4H2PO4 as raw materials, mixing and grinding the raw materials and then adopting a high temperature curing method.

[0025] A preferred solution is to prepare rare earth phosphate by high temperature solidification method, comprising the following steps:

[0026] 1) Raw material mixing: rare earth metal oxide and NH4H2PO4 are used as raw materials, the raw materials are mixed in a mortar according to the stoichiometric ratio, and then ground for 35 to 45 minutes, and the ground raw material mixture is transferred to a crucible;

[0027] 2) Raw material pre-sintering: Place the crucible containing the raw material mixture in a muffle furnace, first heat it to 300°C at a rate of 1°C / min, keep it warm for 3.5-4.5 hours, then heat it to 950°C at a rate of 1°C / min, keep it warm for 10-14 hours, cool it down to room temperature naturally, take it out, and obtain the product after the first sintering;

[0028] 3) Grinding and sintering again: transfer the product after the first sintering to a mortar and grind for 25 to 35 minutes, transfer the ground product to a crucible, put the crucible into the muffle furnace again, and then heat it to 950°C at a rate of 5°C / min, keep it warm for 900 to 1100 minutes, and obtain powdered rare earth phosphate.

[0029] A method for preparing the rare earth phosphate liquid anti-rust coating of the present invention comprises the following steps:

[0030] a) Stir and mix a certain amount of deionized water, a certain amount of pH regulator, a certain amount of dispersant and wetting agent, and a certain amount of defoamer evenly;

[0031] b) adding a proportion of rare earth phosphate and stirring to mix evenly;

[0032] c) Add the proportion of acrylic resin and alcohol ester XII and the remaining proportion of deionized water, and stir to mix evenly;

[0033] d) Add the remaining amount of defoamer, the amount of leveling agent, 30% sodium nitrite aqueous solution, thickener and antibacterial agent, stir and mix evenly to obtain a rare earth phosphate liquid anti-rust coating.

[0034] Compared with the prior art, the present invention has the following significant beneficial effects:

[0035] The invention uses rare earth phosphate as an anti-rust filler, and the obtained water-based coating has good anti-rust performance, is green and environmentally friendly, and also has excellent mechanical properties and hydrophobicity, and has excellent comprehensive performance; in addition, the preparation method of the invention is economical and practical, the preparation process is simple, the cost is low, no special equipment and harsh conditions are required, and large-scale production is easy to achieve, and it has extremely strong industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 FT-IR analysis chart of rare earth phosphate CePO4 prepared in Example 1 of the present invention;

[0037] Figure 2 XRD analysis diagram of rare earth phosphate CePO4 prepared in Example 1 of the present invention;

[0038] Figure 3This is a SEM analysis diagram of the rare earth phosphate CePO4 prepared in Example 1 of the present invention;

[0039] Figure 4 FT-IR analysis chart of the rare earth phosphate GdPO4 prepared in Example 2 of the present invention;

[0040] Figure 5 XRD analysis diagram of the rare earth phosphate GdPO4 prepared in Example 2 of the present invention;

[0041] Figure 6 This is a SEM analysis diagram of the rare earth phosphate GdPO4 prepared in Example 2 of the present invention;

[0042] Figure 7 The following are the actual photos of the rare earth phosphate CePO4 water-based anti-rust coating prepared in Example 3 of the present invention after coating. In the figure, (a) is the actual photo of the coating when the dispersant is G5040 and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; (b) is the actual photo of the coating when the dispersant is G5100 and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively;

[0043] Figure 8 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5040, in which the coating film thickness of the coating is 60 μm, and the addition amount of the filler CePO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0044] Fig. 9 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5040, in which the coating film thickness of the coating is 150 μm, and the addition amount of the filler CePO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0045] Fig.10 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5100, in which the coating film thickness of the coating is 60 μm, and the addition amount of the filler CePO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0046] Fig.11 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5100, in which the coating film thickness of the coating is 150 μm, and the addition amount of the filler CePO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0047] Fig.12The following are photos of the rare earth phosphate GdPO4 water-based antirust coating prepared in Example 4 of the present invention after coating. In the figure, (a) is a photo of the coating when the dispersant G5040 is added in an amount of 1g, 2g, 3g, and 4g of filler GdPO4, respectively; (b) is a photo of the coating when the dispersant G5100 is added in an amount of 1g, 2g, 3g, and 4g of filler GdPO4, respectively;

[0048] Fig.13 The water contact angle measurement result of the rare earth phosphate GdPO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5040, in which the coating film thickness of the coating is 60 μm, and the addition amount of the filler GdPO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0049] Fig.14 The water contact angle measurement result of the rare earth phosphate GdPO4 water-based antirust coating prepared in Example 3 of the present invention with the dispersant being G5040, in which the coating film thickness of the coating is 150 μm, and the addition amount of the filler GdPO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0050] Fig.15 The results of measuring the water contact angle of the water-based antirust coating of the rare earth phosphate GdPO4 prepared in Example 3 of the present invention with the dispersant being G5100 are shown in the figure. In the figure, the coating film thickness of the coating is 60 μm, and the addition amount of the filler GdPO4 is 1 g, 2 g, 3 g, and 4 g, respectively;

[0051] Fig.16 This is a graph showing the water contact angle measurement results of a water-based anti-rust coating of rare earth phosphate GdPO4 prepared in Example 3 of the present invention with the dispersant being G5100. In the graph, the coating film thickness of the coating is 150 μm, and the addition amounts of the filler GdPO4 are 1 g, 2 g, 3 g, and 4 g, respectively. DETAILED DESCRIPTION

[0052] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0053] Example 1

[0054] Preparation of rare earth phosphate CePO4:

[0055] 1) Raw material mixing: CeO2 and NH4H2PO4 are used as raw materials. The raw materials are mixed in a mortar according to the stoichiometric ratio and ground for 40 minutes. The ground raw material mixture is transferred to a crucible;

[0056] 2) Raw material pre-sintering: Place the crucible containing the raw material mixture in a muffle furnace, first heat it to 300°C at a rate of 1°C / min, keep it at that temperature for 4 hours (to decompose the ammonia in NH4H2PO4), then heat it to 950°C at a rate of 1°C / min, keep it at that temperature for 12 hours, cool it down to room temperature naturally, take it out, and obtain the product after the first sintering;

[0057] 3) Grinding and sintering again: transfer the product after the first sintering to a mortar and grind for 30 minutes, transfer the ground product to a crucible, put the crucible into the muffle furnace again, and then heat it to 950°C at a rate of 5°C / min, keep it warm for 1000 minutes, and obtain powdered rare earth phosphate CePO4.

[0058] Figure 1 This is the FT-IR analysis of the rare earth phosphate CePO4 prepared in this example. -1 There is a significant large broadband absorption peak in the region caused by the H-O-H stretching vibration of the H2O molecules between the products and the symmetric compression of the -OH oxygen-hydrogen bond; at 1650cm -1 The torsional vibration peak of the -OH oxygen-hydrogen bond of crystal water appears at 1047 cm -1 A peak caused by PO stretching vibration appears at the position.

[0059] Figure 2 This is the XRD analysis diagram of the rare earth phosphate CePO4 prepared in this embodiment. It can be seen from the figure that the XRD spectrum of CePO4 prepared in this embodiment is basically consistent with the standard XRD spectrum of CePO4 in the database.

[0060] Figure 3 This is a SEM analysis diagram of the rare earth phosphate CePO4 prepared in this embodiment. It can be seen from the figure that the CePO4 sample prepared in this embodiment is in the form of aggregated particles. The sample particles are small and relatively uniform, with a size of about 20-50nm, which is at the nanometer level.

[0061] Example 2

[0062] Preparation of rare earth phosphate GdPO4:

[0063] 1) Raw material mixing: Gd2O3 and NH4H2PO4 were used as raw materials. The raw materials were mixed in a mortar according to the stoichiometric ratio and ground for 40 minutes. The ground raw material mixture was transferred to a crucible.

[0064] 2) Raw material pre-sintering: Place the crucible containing the raw material mixture in a muffle furnace, first heat it to 300°C at a rate of 1°C / min, keep it at that temperature for 4 hours (to decompose the ammonia in NH4H2PO4), then heat it to 950°C at a rate of 1°C / min, keep it at that temperature for 12 hours, cool it down to room temperature naturally, take it out, and obtain the product after the first sintering;

[0065] 3) Grinding and sintering again: The product after the first sintering was transferred to a mortar and ground for 30 minutes. The ground product was transferred to a crucible, and the crucible was placed in the muffle furnace again. The temperature was then increased to 950°C at a rate of 5°C / min and kept at this temperature for 1000 minutes to obtain powdered rare earth phosphate GdPO4.

[0066] Figure 4 This is the FT-IR analysis of the rare earth phosphate GdPO4 prepared in this example. -1 There is a significant large broadband absorption peak in the region caused by the H-O-H stretching vibration of the H2O molecules between the products and the symmetric compression of the -OH oxygen-hydrogen bond; at 1650cm -1 The torsional vibration peak of the -OH oxygen-hydrogen bond of crystal water appears at 1047 cm -1 A peak caused by PO stretching vibration appears at the position.

[0067] Figure 5 This is the XRD analysis diagram of the rare earth phosphate GdPO4 prepared in this embodiment. It can be seen from the figure that the XRD spectrum of GdPO4 prepared in this embodiment is basically consistent with the standard XRD spectrum of GdPO4 in the database.

[0068] Figure 6 This is a SEM analysis diagram of the rare earth phosphate GdPO4 prepared in this embodiment. It can be seen from the figure that the GdPO4 sample prepared in this embodiment is in the form of square particles with a size of about 50-100nm, which is at the nanometer level.

[0069] Example 3

[0070] Preparation of rare earth phosphate CePO4 water-based anti-rust coating:

[0071] a) Mix 12g of deionized water, 0.2g of pH regulator DMAE, 0.4g of dispersant (G5040 or G5100), 0.2g of wetting agent, and 0.2g of defoamer by stirring at a speed of 200-400r / min for 10 minutes in a disperser until uniform;

[0072] b) Add rare earth phosphate CePO4 (1g, 2g, 3g, 4g respectively), stir at 800-900r / min for 1 hour in a disperser to mix evenly;

[0073] c) Add 50g D012 acrylic resin latex, 0.8g alcohol ester twelve, and 0.8g deionized water, and stir at 300-400r / min for 10 minutes in a disperser to mix evenly;

[0074] d) Add 0.1g of defoamer, 0.2g of leveling agent, 0.1g of 30% sodium nitrite aqueous solution, 0.2g of thickener, and 0.1g of 10% DF35 aqueous solution, stir at a speed of 300-400r / min for 10 minutes in a disperser, and mix evenly to obtain a rare earth phosphate CePO4 water-based anti-rust coating.

[0075] The tinplate is first ground and then cleaned with anhydrous ethanol. This operation is repeated twice to obtain a tinplate with a rough surface. The treated tinplate is used as a test substrate, and the prepared rare earth phosphate CePO4 water-based anti-rust coating is evenly applied to the tinplate, and the physical and chemical properties of the coating are tested.

[0076] 3.1 Physical performance test of rare earth phosphate CePO4 water-based anti-rust coating:

[0077] The coatings doped with different contents of CePO4 were uniformly coated on the tinplate with a thickness of 60μm and 150μm, respectively. The tinplate was sent into an oven, and the drying time, film thickness and glossiness of the coatings were tested. The test results are shown in Table 1 and Figure 7 shown.

[0078] Table 1 Physical properties of rare earth phosphate CePO4 water-based anti-rust coating

[0079]

[0080] As can be seen from Table 1, the rare earth phosphate CePO4 water-based anti-rust coating prepared in this embodiment has good physical properties such as solid content, viscosity, drying time, glossiness, etc., and the viscosity of the coating when the dispersant is 5040 is greater than the viscosity of the coating when the dispersant is 5100.

[0081] Figure 7The following are actual photographs of the rare earth phosphate CePO4 water-based anti-rust coating prepared in this embodiment after coating. In the figure, (a) is the actual photograph of the coating when the dispersant is G5040 and the added amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; (b) is the actual photograph of the coating when the dispersant is G5100 and the added amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively. It can be seen from the figure that the color of the coating prepared in this embodiment after coating on the tinplate and hardening is opaque, similar to a ceramic body, the surface of the coating is flat without protrusions, and there are no bubbles or powder falling, indicating that the coating of the coating has no defects in its macroscopic morphology.

[0082] 3.2 Mechanical properties test of rare earth phosphate CePO4 water-based anti-rust coating:

[0083] The mechanical properties of the coating, such as film thickness, adhesion, and pencil hardness, were tested. The test results are shown in Table 2.

[0084] Table 2 Mechanical properties test data of rare earth phosphate CePO4 water-based anti-rust coating

[0085]

[0086] It can be seen from Table 2 that the rare earth phosphate CePO4 water-based anti-rust coating prepared in this embodiment has excellent pencil hardness and adhesion, excellent mechanical properties, and the adhesion is positively correlated with the amount of filler added, and the adhesion of the coating when the dispersant is 5040 is better than the adhesion of the coating when the dispersant is 5100, that is, the coating with dispersant G5040 can adhere to the substrate more effectively than the coating with dispersant G5100, and is less likely to peel off the coating.

[0087] 3.3 Water contact angle test of rare earth phosphate CePO4 water-based anti-rust coating

[0088] After the coating is applied to the tinplate and dried, the coated plate is placed on the test bench with a syringe, and ionized water is applied to the surface of the coating film with a syringe. The angle between the gas-liquid interface and the liquid-solid interface is measured by a contact angle measuring instrument. Three different positions on the coated plate are selected for each measurement, and the measured data are averaged. In this way, the water contact angle data of the coating under different film thicknesses are measured, and the hydrophilicity and hydrophobicity of the coating are characterized by the water contact angle data. The measurement results are shown in Figure 8-Figure 11 shown.

[0089] Figure 8 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in this embodiment with the dispersant G5040 is shown in the figure. In the figure, the coating film thickness of the coating is 60 μm, and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; Fig. 9The water contact angle of the water-based antirust coating of rare earth phosphate CePO4 prepared in this embodiment with the dispersant G5040 is measured. In the figure, the coating film thickness of the coating is 150 μm, and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; Figure 8 and Fig. 9 It can be seen that when the dispersant G5040 is used in this embodiment, the water contact angle of the coating is close to 90 degrees, which has a certain hydrophobicity. When the addition amount of filler CePO4 is 4g, the water contact angle is the largest and the hydrophobicity is the strongest. The enhanced hydrophobicity helps to protect the metal substrate from corrosion. The maximum contact angle when the coating thickness is 150μm is greater than the maximum contact angle when the coating thickness is 60μm, indicating that the thickness of the film has a certain influence on the contact angle of the coating.

[0090] Fig.10 The water contact angle measurement result of the rare earth phosphate CePO4 water-based antirust coating prepared in this embodiment with the dispersant G5100 is shown in the figure. In the figure, the coating film thickness of the coating is 60 μm, and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; Fig.11 The water contact angle of the water-based antirust coating of rare earth phosphate CePO4 prepared in this embodiment with the dispersant G5100 is measured. In the figure, the coating film thickness of the coating is 150 μm, and the addition amount of filler CePO4 is 1g, 2g, 3g, and 4g respectively; Fig.10 and Fig.11 It can be seen that when the dispersant G5100 is used in this embodiment, the water contact angle of the coating is close to 90 degrees, which has a certain hydrophobicity, and the contact angle tends to be stable after the addition amount of filler CePO4 exceeds 2g, indicating that when G5100 is used as the coating dispersant, the thickness of the film has little effect on the contact angle of the coating.

[0091] 3.4 Salt spray resistance test of rare earth phosphate CePO4 water-based anti-rust coating

[0092] The durability of the coating under neutral salt spray conditions was tested according to standard GB / T 1771-2007.

[0093] Apply the coating evenly on the treated tinplate and seal the edges with rosin paraffin. During the edge sealing process, the paraffin needs to be heated and slowly moved around the tinplate to pour the coating around the tinplate little by little. After sealing the tinplate around, place it in a salt spray box for continuous spraying. Check the erosion every 12 hours and put it back after observation.

[0094] The tinplate was polished with 80-grit sandpaper, cleaned with alcohol, sprayed with paint, and then placed in an indoor environment for a week before starting the experimental test. In order to prevent rust, the edge of the steel plate was sealed with plastic tape before the test, and then the specimen was placed in a salt spray chamber, and its corrosion was checked every 12 hours, and then put back in place after observation.

[0095] The test results show:

[0096] When the film thickness is 60 μm and the dispersant is G5040 or G5100: the tinplate plate without coating on the surface has shown serious rust after 72 hours, and is completely corroded after 120 hours, and the rust area reaches 100%; while the tinplate plate with different contents of fillers coated on the surface is still flat and smooth after 180 hours, without rust. The edge of the coated plate begins to rust after 360 hours and is completely corroded after 720 hours. However, the hardness of the coating does not change due to the rust, and it can adhere well to the tinplate plate and has good bonding properties; This shows that the rare earth phosphate CePO4 water-based anti-rust coating prepared in this embodiment has good salt spray resistance and excellent anti-rust ability.

[0097] Example 4

[0098] Preparation of rare earth phosphate GdPO4 water-based anti-rust coating:

[0099] a) Mix 12g of deionized water, 0.2g of pH regulator DMAE, 0.4g of dispersant (G5040 or G5100), 0.2g of wetting agent, and 0.2g of defoamer by stirring at a speed of 200-400r / min for 10 minutes in a disperser until uniform;

[0100] b) Add rare earth phosphate GdPO4 (1g, 2g, 3g, 4g respectively), stir at 800-900r / min for 1 hour in a disperser to mix evenly;

[0101] c) Add 50g D012 acrylic resin latex, 0.8g alcohol ester twelve, and 0.8g deionized water, and stir at 300-400r / min for 10 minutes in a disperser to mix evenly;

[0102] d) Add 0.1g of defoamer, 0.2g of leveling agent, 0.1g of 30% sodium nitrite aqueous solution, 0.2g of thickener, and 0.1g of 10% DF35 aqueous solution, stir at a speed of 300-400r / min for 10 minutes in a disperser, and mix evenly to obtain a rare earth phosphate GdPO4 water-based anti-rust coating.

[0103] The tinplate is first ground and then cleaned with anhydrous ethanol. This operation is repeated twice to obtain a tinplate with a rough surface. The treated tinplate is used as a test substrate, and the prepared rare earth phosphate GdPO4 water-based anti-rust coating is evenly applied to the tinplate, and the physical and chemical properties of the coating are tested.

[0104] 4.1 Physical performance test of rare earth phosphate GdPO4 water-based anti-rust coating:

[0105] The coatings doped with different contents of GdPO4 were uniformly coated on the tinplate with a thickness of 60μm and 150μm, and the tinplate was sent into the oven to test the drying time, film thickness and glossiness of the coatings. The test results are shown in Table 3 and Fig.12 shown.

[0106] Table 3 Physical properties of rare earth phosphate GdPO4 water-based anti-rust coating

[0107]

[0108] Combining Table 1 and Table 3, it can be seen that the rare earth phosphate GdPO4 water-based anti-rust coating prepared in this embodiment has good physical properties such as solid content, viscosity, drying time, gloss, etc., and when the dispersant is 5040, the viscosity of the coating is inversely proportional to the filler content, and the other properties are similar to those of the CePO4 coating. At the same time, the drying time of the coating increases with the increase in the proportion of fillers.

[0109] Fig.12 The following are actual photographs of the rare earth phosphate GdPO4 water-based anti-rust coating prepared in this embodiment after coating. In the figure, (a) is a actual photograph of the coating when the dispersant is G5040 and the added amount of filler GdPO4 is 1g, 2g, 3g, and 4g respectively; (b) is a actual photograph of the coating when the dispersant is G5100 and the added amount of filler GdPO4 is 1g, 2g, 3g, and 4g respectively. It can be seen from the figure that the color of the coating prepared in this embodiment after coating on the tinplate is hardened is opaque, and the surface of the coating is smooth, indicating that the coating of the coating has no defects in terms of macroscopic morphology.

[0110] 4.2 Mechanical properties test of rare earth phosphate GdPO4 water-based anti-rust coating:

[0111] The mechanical properties of the coating, such as film thickness, adhesion, and pencil hardness, were tested, and the test results are shown in Table 4.

[0112] Table 4 Mechanical properties test data of rare earth phosphate GdPO4 water-based anti-rust coating

[0113]

[0114] Combining Table 2 and Table 4, it can be seen that the rare earth phosphate GdPO4 water-based anti-rust coating prepared in this embodiment has excellent pencil hardness and adhesion, excellent mechanical properties, and compared with CePO4 coating, GdPO4 coating has better adhesion, can be more effectively adhered to the substrate, and is less likely to peel off the coating.

[0115] 4.3 Water contact angle test of rare earth phosphate GdPO4 water-based anti-rust coating

[0116] After the coating is applied to the tinplate and dried, the coated plate is placed on the test bench with a syringe, and ionized water is applied to the surface of the coating film with a syringe. The angle between the gas-liquid interface and the liquid-solid interface is measured by a contact angle measuring instrument. Three different positions on the coated plate are selected for each measurement, and the measured data are averaged. In this way, the water contact angle data of the coating under different film thicknesses are measured, and the hydrophilicity and hydrophobicity of the coating are characterized by the water contact angle data. The measurement results are shown in Figure 13-Figure 16 shown.

[0117] Fig.13 The water contact angle measurement result of the rare earth phosphate GdPO4 water-based antirust coating prepared in this embodiment with the dispersant G5040 is shown in the figure. In the figure, the coating film thickness of the coating is 60 μm, and the addition amount of the filler GdPO4 is 1g, 2g, 3g, and 4g respectively; Fig.14 The water contact angle of the water-based antirust coating of rare earth phosphate GdPO4 prepared in this embodiment with the dispersant G5040 as the test result is shown in the figure. In the figure, the coating film thickness of the coating is 150 μm, and the addition amount of filler GdPO4 is 1g, 2g, 3g, and 4g respectively; Fig.13 and Fig.14 It can be seen that when the dispersant G5040 is used in this embodiment, the water contact angle of the coating is close to 90 degrees, which has a certain hydrophobicity. In general, the water contact angle of the GdPO4 coating is smaller than that of the CePO4 coating, indicating that the hydrophobicity of the GdPO4 coating is slightly worse than that of the CePO4 coating.

[0118] Fig.15 The water contact angle measurement result of the rare earth phosphate GdPO4 water-based antirust coating prepared in this embodiment with the dispersant G5100 is shown in the figure. In the figure, the coating film thickness of the coating is 60 μm, and the addition amount of the filler GdPO4 is 1g, 2g, 3g, and 4g respectively; Fig.16 The water contact angle of the water-based antirust coating of the rare earth phosphate GdPO4 prepared in this embodiment with the dispersant G5100 as the test result is shown in the figure. In the figure, the coating film thickness of the coating is 150 μm, and the addition amount of the filler GdPO4 is 1g, 2g, 3g, and 4g respectively; Fig.15 and Fig.16It can be seen that when the dispersant G5100 is used in this embodiment, the water contact angle of the coating is close to 90 degrees, which has a certain hydrophobicity. In general, the water contact angle of the GdPO4 coating is smaller than that of the CePO4 coating, indicating that the hydrophobicity of the CePO4 water-based anti-rust coating is better than that of the GdPO4 water-based anti-rust coating.

[0119] comprehensive Figure 8-Figure 11 , Figure 13-Figure 16 It can be seen that the rare earth phosphate water-based antirust coatings prepared by the present invention have a certain hydrophobicity, and the hydrophobicity of the CePO4 water-based antirust coating is better than that of the GdPO4 water-based antirust coating, and the hydrophobicity of the coating with the G5040 dispersant is better than that of the coating with the G5100 dispersant.

[0120] 4.4 Salt spray resistance test of rare earth phosphate GdPO4 water-based anti-rust coating

[0121] The durability of the coating under neutral salt spray conditions was tested according to standard GB / T 1771-2007.

[0122] Apply the coating evenly on the treated tinplate and seal the edges with rosin paraffin. During the edge sealing process, the paraffin needs to be heated and slowly moved around the tinplate to pour the coating around the tinplate little by little. After sealing the tinplate around, place it in a salt spray box for continuous spraying. Check the erosion every 12 hours and put it back after observation.

[0123] The tinplate was polished with 80-grit sandpaper, cleaned with alcohol, sprayed with paint, and then placed in an indoor environment for a week before starting the experimental test. In order to prevent rust, the edge of the steel plate was sealed with plastic tape before the test, and then the specimen was placed in a salt spray chamber, and its corrosion was checked every 12 hours, and then put back in place after observation.

[0124] The test results show:

[0125] When the film thickness is 60 μm and the dispersant is G5040 or G5100: the tinplate without coating on the surface has shown serious corrosion after 72 hours, and is completely corroded after 120 hours, and the corrosion area reaches 100%; while the tinplate with different contents of fillers coated on the surface begins to rust after 240 hours. After 360 hours, there is no shedding of the coating surface, and the edge of the iron plate is corroded. At the same time, the hardness of the coating does not decrease, and the adhesion performance to the iron plate is good; This shows that the rare earth phosphate GdPO4 water-based anti-rust coating prepared in this embodiment has good salt spray resistance and excellent anti-rust ability.

[0126] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.

Claims

1. A rare earth phosphate liquid anti-rust coating, characterized in that: It has the following composition and ratio: Deionized water: 12-14 parts by weight; Acrylic resin: 50-55 parts by mass; Dispersant: 4.0~4.5 parts by mass; Wetting agent: 0.2~0.4 parts by mass; PH regulator: 0.2~0.5 parts by mass; Defoaming agent: 0.3~0.5 parts by mass; Alcohol ester twelve: 0.8~1 parts by mass; Leveling agent: 0.2~0.3 parts by mass; Thickener: 0.1~0.3 parts by mass; 30% sodium nitrite aqueous solution: 0.1-0.2 parts by mass; Antibacterial agent: 0.05~0.1 parts by mass; Rare earth phosphate: 1-4 parts by mass.

2. The rare earth phosphate liquid antirust coating according to claim 1, characterized in that: The acrylic resin is D012 acrylic resin latex.

3. The rare earth phosphate liquid antirust coating according to claim 1, characterized in that: The dispersant is selected from any one of dispersants G5040 and G5100; the rare earth phosphate is selected from any one of CePO4 and GdPO4.

4. The rare earth phosphate liquid antirust coating according to claim 1, characterized in that: The wetting agent is wetting agent R-33; the pH regulator is DMAE; the defoaming agent is defoaming agent 825; the leveling agent is leveling agent 3020; the thickener is thickener 105A; and the antibacterial agent is 10% DF35 aqueous solution.

5. The rare earth phosphate liquid antirust coating according to claim 1, characterized in that: The rare earth phosphate is prepared by using rare earth metal oxide and NH4H2PO4 as raw materials, mixing and grinding the raw materials and then adopting a high-temperature curing method.

6. The rare earth phosphate liquid antirust paint according to claim 5, characterized in that: The high temperature solidification method for preparing rare earth phosphates comprises the following steps: 1) Raw material mixing: rare earth metal oxide and NH4H2PO4 are used as raw materials, the raw materials are mixed in a mortar according to the stoichiometric ratio, and then ground for 35 to 45 minutes, and the ground raw material mixture is transferred to a crucible; 2) Raw material pre-sintering: Place the crucible containing the raw material mixture in a muffle furnace, first heat it to 300°C at a rate of 1°C / min, keep it warm for 3.5-4.5 hours, then heat it to 950°C at a rate of 1°C / min, keep it warm for 10-14 hours, cool it down to room temperature naturally, take it out, and obtain the product after the first sintering; 3) Grinding and sintering again: transfer the product after the first sintering to a mortar and grind for 25 to 35 minutes, transfer the ground product to a crucible, put the crucible into the muffle furnace again, and then heat it to 950°C at a rate of 5°C / min, keep it warm for 900 to 1100 minutes, and obtain powdered rare earth phosphate.

7. A method for preparing the rare earth phosphate liquid anti-rust coating according to claim 1, characterized in that: The steps include: a) Stir and mix a certain amount of deionized water, a certain amount of pH regulator, a certain amount of dispersant and wetting agent, and a certain amount of defoamer evenly; b) adding a proportion of rare earth phosphate and stirring to mix evenly; c) Add the proportion of acrylic resin and alcohol ester XII and the remaining proportion of deionized water, and stir to mix evenly; d) Add the remaining amount of defoamer, the amount of leveling agent, 30% sodium nitrite aqueous solution, thickener and antibacterial agent, stir and mix evenly to obtain a rare earth phosphate liquid anti-rust coating.

Citation Information

Patent Citations

  • Solvent-thermal synthesis of lanthanum phosphate nanorod

    CN101323442A

  • Aqueous rust resisting paint and preparation method thereof

    CN102477242A

  • Fireproof forsterite coating and preparation method thereof

    CN107235737A

  • Aqueous environmentally friendly anticorrosion paint for metals and preparation method thereof

    CN108929581A

  • Ion-crosslinking based treating agent for self-deposition coating film, and preparation method and application thereof

    CN110054966A